2011
DOI: 10.1080/01431161.2011.606240
|View full text |Cite
|
Sign up to set email alerts
|

Combining optical satellite data and airborne laser scanner data for vegetation classification

Abstract: The aim of this study was to investigate to which degree the accuracy of vegetation classification could be improved by combining optical satellite data and airborne laser scanner (ALS) data, compared with using satellite data only. A Satellite Pour l'Observation de la Terre (SPOT) 5 scene and Leica ALS 50-II data from 2009, covering a test area in the mid-Sweden (latitude 60° 43' N, longitude 16° 43' E), were used in maximum likelihood and decision tree classifications. Training and validation data were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 17 publications
2
4
0
1
Order By: Relevance
“…The superiority of CART was also observed by Mallinis, et al [22] who found that CART improved classification accuracy by over 20% compared to NN approach in classifying natural forest in Northern Greece. The improvement of sensor fusion shown here is consistent with what other studies have found although the amount of improvement in this study appears lower compared to Bork and Su [8] and Nordkvist, et al [9], who saw a 15-20% improvement when combining LiDAR surfaces with optical sensors. Using only RapidEye enables the capture of plantations reasonably well; giving a minimum producer's accuracy of 80% and a minimum user's accuracy of 83% both achieved by NN-RE only.…”
Section: Initial Land Cover Classificationsupporting
confidence: 76%
See 1 more Smart Citation
“…The superiority of CART was also observed by Mallinis, et al [22] who found that CART improved classification accuracy by over 20% compared to NN approach in classifying natural forest in Northern Greece. The improvement of sensor fusion shown here is consistent with what other studies have found although the amount of improvement in this study appears lower compared to Bork and Su [8] and Nordkvist, et al [9], who saw a 15-20% improvement when combining LiDAR surfaces with optical sensors. Using only RapidEye enables the capture of plantations reasonably well; giving a minimum producer's accuracy of 80% and a minimum user's accuracy of 83% both achieved by NN-RE only.…”
Section: Initial Land Cover Classificationsupporting
confidence: 76%
“…After excluding the harvested area and new plantings due to temporal differences between the aerial photography and satellite imagery, the producer's accuracy of plantation increased to 89%. The mapping approach used here has produced classification results comparable to previous studies [9,13,23,28,49]. The accuracy of the method was further examined by comparing the mapped plantation area with manually digitised plantation area.…”
Section: Discussionsupporting
confidence: 53%
“…The majority of research on using height data in combination with spectral data for the classification of vegetation has been primarily made related to forestry (e.g., [9][10][11]). However, there are considerable differences in height and spatial extent between trees and aquatic plants.…”
Section: Introductionmentioning
confidence: 99%
“…Although primarily collected for the purpose of constructing a new national terrain model (or digital elevation model; DEM), the collected lidar data is also used by SLU on behalf of the Swedish Forest Agency for constructing a nationwide forest database [10]. Furthermore, it has been shown in earlier studies that lidar data is an excellent complement to optical satellite data for land cover classification, especially for the characterization of tree vegetation [11,12].…”
Section: Introductionmentioning
confidence: 99%